The Parent Swap Shop - Simon, Francesca; Illustrator, Pete Williamson (London, Orion Children's Books, 2011)
"Ava is sick and tired of her parents always telling her what to do. Then she sees an advert for the Parent Swap Shop. Maybe it's time to trade in the old ones for a new and improved mum and dad ..."--Back cover. Suggested level: junior, primary
A1 shelf
Keywords: English fiction story book